To the Issue of the Comparison of 2D and 3D Modeling of Mechanical-Engineering Parts - Rudnitskaya, Anastasia V.; Sokolov, Semeon A.; Fedotov, Gennady V. (2024 7th International Conference on Information Technologies in Engineering Education (Inforino), 2024)
The article provides a comparison of two methods for designing mechanical engineering parts using 2D and 3D modeling according to the following criteria:*speed of creating models.*responsibilities for creating models.*project editing capabilities.*information content of the model.*methods of manufacturing parts.As examples, assignments from the course "Engineering and Computer Graphics" of the Department of Modeling and Design of Power Installations (MDPI) of the National Research University "MPEI" were used, which the authors, students of this article, completed on the nanoCAD system.The authors believe that the course program "Engineering and Computer Graphics" of the Department of MDPI National Researching University "MPEI" is effective and relevant; the use of 3D modeling without mastering 2D modeling is not the right method of specialist education, because the latter provides the necessary skills in engineering graphics of complex mechanical-engineering parts.